Development of a novel niosomal system for oral delivery of Ginkgo biloba extract - Jin, Ye (Dove Medical Press, 2013)
BACKGROUND: The aim of this study was to develop an optimal niosomal system to deliver Ginkgo biloba extract (GbE) with improved oral bioavailability and to replace the conventional GbE tablets. METHODS: In this study, the film dispersion-homogenization method was used to prepare GbE niosomes. The resulting GbE niosome suspension was freeze-dried or spray-dried to improve the stability of the niosomes. GbE-loaded niosomes were formulated and characterized in terms of their morphology, particle size, zeta potential, entrapment efficiency, and angle of repose, and differential scanning calorimetry analysis was performed. In vitro release and in vivo distribution studies were also carried out. RESULTS: The particle size of the optimal delivery system prepared with Tween 80, Span 80, and cholesterol was about 141 nm. There was a significant difference (P < 0.05) in drug entrapment efficiency between the spray-drying method (about 77.5%) and the freeze-drying method (about 50.1%). The stability study revealed no significant change in drug entrapment efficiency for the GbE niosomes at 4°C and 25°C after 3 months. The in vitro release study suggested that GbE niosomes can prolong the release of flavonoid glycosides in phosphate-buffered solution (pH 6.8) for up to 48 hours. The in vivo distribution study showed that the flavonoid glycoside content in the heart, lung, kidney, brain, and blood of rats treated with the GbE niosome carrier system was greater than in the rats treated with the oral GbE tablet (P < 0.01). No flavonoid glycosides were detected in the brain tissue of rats given the oral GbE tablets, but they were detected in the brain tissue of rats given the GbE niosomes. CONCLUSION: Niosomes are a promising oral system for delivery of GbE to the brain.